Analysis of Carrying Capacity as Strengthening Reinforcement in the Achievement Challenge of National Student Sports Olympic Athletes - Mahmun Saripudin; Muhammad Nur Alif; Rizal Ahmad Fauzi (Tadulako Journal Sport Sciences And Physical Education, 2026)
The development of early childhood athletes at the elementary school level has a strategic role in forming a sustainable foundation of skills, character, and sports achievements. This study aims to analyze the supporting capacity of sports facilities and infrastructure as well as the role of non-physical reinforcement in developing the achievements of athletes participating in the National Student Sports Olympiad (O2SN) at the elementary school level. This study uses a qualitative approach with a case study design carried out in five State Elementary Schools in Rancakalong District, Sumedang Regency. The study participants consisted of student athletes, Physical Education teachers, and principals who were selected purposively based on their involvement in the development of athletes. Data was collected through interviews, observations, and documentation, then analyzed thematically through the stages of data reduction, categorization, and conclusion drawn. The results of the study show that the availability of sports facilities and infrastructure is not even and has not fully supported technical development in several sports. However, limited facilities are not the main factor that hinders achievement. Non-physical reinforcement that is consistently provided through motivation, technical guidance, appreciation, school policies, and parental support plays a dominant role in maintaining athlete motivation, training consistency, and confidence. Thus, facilities and infrastructure function as supporting factors, while psychological, social, and managerial strengthening is the main factor in improving athletes' achievements in elementary school. This research contributes to strengthening the school-based athlete coaching model in the context of limited facilities.